Rekonstruksi Ontologis Manajemen Pendidikan Berbasis Filsafat Ilmu di Era Disrupsi - Hendrian Yonata; Priski Setiawan (Alpatih Harapan Semesta, 2025)
This research aims to examine the ontological foundation of science in the development of educational management paradigms in the era of disruption by exploring the nature of educational management reality from the perspective of the philosophy of science. The main issue raised is the tendency of educational management studies to remain technical-instrumental and not yet deeply address the philosophical aspects, particularly the ontology of science. This research uses a qualitative approach through a literature study of books on the philosophy of science, educational management, as well as reputable national and international journal articles. The study results show that educational management ontologically is a complex, dynamic, and contextual social reality, formed from the interaction between structure, actors, values, and environmental changes. Therefore, the development of educational management paradigms in the era of disruption needs to be based on an integrative, adaptive, and reflective ontology in order to address the challenges of sustainable educational change.